GENDER CHARACTERISTICS OF PEDAGOGICAL SPEECH - SABIROVA, Dildora Abduvaliyevna (The Lingua Spectrum, 2025)
This article provides a comprehensive investigation into the gender characteristics of pedagogical speech, drawing directly on the theories and empirical findings of Tannen (1994), Coates (2015), Holmes (2008), Myhill (2002), Jones & Myhill (2007), Sunderland (2006), Pavlenko (2014), and related foundational scholars in gender linguistics. The study synthesizes discourse analysis, sociolinguistic evidence, and classroom interaction research to reveal how gendered identity, politeness strategies, power relations, and discursive patterns shape teacher talk. Results demonstrate that women generally adopt rapport-oriented, mitigated, collaborative, and affiliative communicative strategies, while men tend toward directive, authoritative, and task-oriented communication. These tendencies vary across cultural, institutional, and situational contexts, revealing the complexity of gendered pedagogical discourse. Implications for teacher education, inclusive pedagogy, and classroom communication are discussed.